2007
DOI: 10.2337/db06-0518
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Induces Intestinal Insulin Resistance and Stimulates the Overproduction of Intestinal Apolipoprotein B48-Containing Lipoproteins

Abstract: There is growing evidence suggesting intestinal insulin resistance and overproduction of apolipoprotein (apo) B48 -containing chylomicrons in insulin-resistant states. In the current study, we investigated the potential role of the inflammatory cytokine tumor necrosis factor-␣ (TNF-␣) in the development of insulin resistance and aberrant lipoprotein metabolism in the small intestine in a Syrian golden hamster model. TNF-␣ infusion decreased whole-body insulin sensitivity, based on in vivo euglycemic clamp stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 72 publications
(79 reference statements)
2
79
0
1
Order By: Relevance
“…The right jugular vein and the left carotid artery were exposed under isoflurane anesthesia, and hamsters were inserted with catheters encased in silastic tubing that were exteriorized to the back of the neck (48,49). Following an overnight recovery period and a 16-h fast, a 4-h infusion of 0.9% normal saline (vehicle) or TNF-␣ (0.5 g/kg per h) was administered by the venous catheter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The right jugular vein and the left carotid artery were exposed under isoflurane anesthesia, and hamsters were inserted with catheters encased in silastic tubing that were exteriorized to the back of the neck (48,49). Following an overnight recovery period and a 16-h fast, a 4-h infusion of 0.9% normal saline (vehicle) or TNF-␣ (0.5 g/kg per h) was administered by the venous catheter.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocytes were lysed, and the immunoprecipitation/immunoblotting protocols were performed as described (49,59,60).…”
Section: Methodsmentioning
confidence: 99%
“…Although we did not rule out the effect of hyperinsulinemia on the intestinal MTP activity and mRNA levels, hyperinsulinemic mice have higher intestinal ( 70 ) and hepatic ( 71 ) MTP expression and plasma triglyceride. Similarly, diabetic men and rabbits have been shown to express signifi cantly higher intestinal MTP mRNA levels compared with nondiabetic subjects ( 72,73 ).…”
Section: Expression Of Lepr Pomc Agrp and Mc4r In Enterocytesmentioning
confidence: 99%
“…MTP activity and protein expression however, were not altered. In the enterocyte of fructose fed golden hamster MTP mRNA and protein mass were increased by tumour necrosis factor(TNF)α but apo B levels in the enterocyte were not effected suggesting that there is considerable inter species variation [91]. In human studies in type 2 diabetes we demonstrated an increase in MTP mRNA in intestinal biopsies [71,90].…”
Section: Microsomal Triglyceride Transfer Proteinmentioning
confidence: 63%
“…In the rabbit increased MTP mRNA is associated with increase in chylomicron particle numbers [88] but in the rat it is associated with larger particles [89]. The fructose-fed insulin resistant hamster model, has an increase in MTP protein mass and this was associated with an increase in the triglyceride-rich intestinally derived lipoproteins [91]. Zolotowska et al [92] in 2003 examined the B48 containing lipoprotein assembly in the small intestine of psamnonys obesus, a model of nutritionally-induced diabetes and insulin resistance.…”
Section: Microsomal Triglyceride Transfer Proteinmentioning
confidence: 99%